The role of kyphoplasty in the management of osteogenesis imperfecta: risk or benefit? - Fürstenberg, Carl Hans; Grieser, Thomas; Wiedenhöfer, Bernd; Gerner, Hans-Jürgen; Putz, Cornelia (European spine journal, 2010)
Kyphoplasty is a recognized treatment option in the management of symptomatic osteoporotic compression fractures, osteolytic vertebral metastases or haemangioma. To our knowledge, kyphoplasty with polymethylmethacrylate in a patient with type I osteogenesis imperfecta (OI) and a vertebral compression fracture has not been reported so far. We report on a 58-year-old patient with type I OI and a vertebral compression fracture at L2 with undislocated posterior vertebral wall and an additional older L1 fracture. Because of severe back pain resistant to conservative therapy over 5 months the indication for percutaneous kyphoplasty was made. Preoperative adjacent endplates of L2 were nearly parallel. Radiologically a minimal loss of height of the L2 vertebra was seen without adjacent fractures at 9 months follow-up. A slight increase of the preoperative kyphotic angle of overlying vertebrae L1 (8.7°/10.3°) and T12 (10.4°/11.0°) was apparent. The visual analogue scale showed decrease of low back pain from 10 to 2 allowing mobilization with a walking frame. Kyphoplasty constitutes a minimal invasive therapeutic alternative in the treatment of vertebral fractures in type I OI and pain, resistant to conservative treatment. Similar to the results of osteoporotic fractures the immediate reduction of pain and stabilization of the fracture in undislocated fragments can be achieved. No adjacent fractures occurred 9 months postoperatively after kyphoplasty in type I OI. Preoperative parallelism of the endplates seems to protect from adjacent fractures.
Online veröffentlicht am 1. Dezember 2009
Gesehen am 17.07.2023